EVALUASI SISTEM PENGENDALIAN MANAJEMEN PADA PELAYANAN PERSAMPAHAN PEMERINTAH KABUPATEN TEMANGGUNG (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
Garbage is a problem that is still homework for most areas, starting from the household scale, village/kelurahan, district, and even national scale. A management control system in solid waste services is very necessary in order to achieve the expected target. The aims of this research are to evaluate the factors that affect the management control system in the waste service of the Temanggung Regency Government that has not reached the expected target and Formulating efforts to improve the management control system in the waste service of the Temanggung Regency Government to achieve the expected target. This research was conducted at the Department of Public Housing, Settlement and Environment Temanggung Regency. The method used in this study uses a qualitative research method with a descriptive approach. The data obtained were analyzed graphically and tabularly, then interpreted comprehensively. The results of the study indicate that the management control system for the waste service of the Temanggung Regency Government has not been able to achieve the expected target due to: a). Jakstrada Temanggung Regency has not been used as a reference for the implementation of waste service activities in the Temanggung Regency Government; b). The budgeting system is not sufficient for the implementation of the target for reducing and handling waste; c). Waste management institutions at the neighborhood level, village/kelurahan, sub-district, and the active involvement of the entire community have not been maximized in reducing and handling waste from sources that have not been running as expected; d). Not yet optimal support for facilities and infrastructure, operational costs, processing technology, and adequate personnel for the implementation of waste management in the TPA; and e). There is no system for controlling, reporting, and analyzing the waste services of the Temanggung Regency Government based on Information Technology and a). improvement of the system and calculation of retribution for waste services that can encourage the community to sort and process waste properly; b). determination of waste management technology at the household scale, village/kelurahan scale, regional scale, and TPA scale for each type of waste; c) technical determination of the segregated waste transportation system; d). additional budget, fleet, and personnel; e). formulating technical cooperation with the private sector in waste management/absorption of waste processing results and opening the widest possible collaboration opportunities with partnership/MoU/CSR schemes to support waste reduction and handling and absorption of waste processing products; g). the formulation of an Information Technology System (IT) for Waste Management in Temanggung Regency which can be accessed for real-time, valid, and accurate data by stakeholders to facilitate evaluation and monitoring of Jakstrada achievements carried ut regularly and follow-up on several indicators that have not been achieved needs to be immediately formulated together; h). strengthening of village waste management institutions, waste banks, and KSM, functions, and implementation of waste reduction and handling in TPSD/TPSKel/TPS3R, human resources for waste management, socialization to the community of waste sorting and processing from the household level; i). strengthening of waste processing at the TPA as a gateway for final waste reduction and handling, fulfillment of waste processing facilities and infrastructure at the TPA; and j). Strengthening regulations regarding rewards and sanctions play an important role in efforts to improve the management control system in the waste services of the Temanggung Regency Government to successfully achieve the waste service targets as mandated by the Temanggung Regent Regulation Number 35 of 2018 concerning Regional Policies and Strategies for the Temanggung Regency in the Management of Household Waste and Waste A Kind of Household Garbage.
Keywords: Waste; Management Control System; Target of Jakstrada Temanggung Regency in the Management of Household Waste and Household Waste Similar